Mengkaji Dampak Sosial Pengembangan Desa Wisata Karangrejo dan Karanganyar, Borobudur, Jawa Tengah - Anggraeni, Anna Rizky; Prastika, Silviana; Lathiif, M. Izza; Tri J., Sausan Adelia Galuh; Dean, Neta Harmisa; N., Rifka Nafilatun (Pusat Studi Pariwisata Universitas Gadjah Mada, 2024)
Local community involvement is one of the main focuses of the concept of sustainable tourism. By emphasizing Community-Based Tourism (CBT), this study examines the impact of tourism on the social conditions of the community in Karangrejo Village and Karanganyar Village, Borobudur District, Magelang Regency, Central Java Province. This study uses a qualitative approach so that data collection can be carried out through interviews and direct observation. Tourism activists such as local business owners and community coordinators in Karangrejo Village and Karanganyar Village are key informants in revealing the socio-community and socio-economic aspects as an impact of tourism. The findings show that tourism has an impact on at least five aspects, namely population, employment, health, education, and community inclusiveness. Serious attention to the importance of inclusive policies is crucial to ensure fair participation for the community in sustainable tourism development practices.